The patent system of the Netherlands in a Belgian mirror, 1817-1869 - Homer Wagenaar (Queen's University Centre for Economic History (QUCEH), 2025)
This paper is an institutional study of the patent systems of the United Kingdom of the Netherlands and its successor states Belgium and the Netherlands in the nineteenth century. The patent law of 1817 gave the state wide discretion to accept or refuse patents and to customise their duration, fees, and terms on a case-by-case basis. Through an indepth reconstruction of the patent system's administrative process, I demonstrate (1) how this system developed informal rules of procedure in its initial years, and (2) how the law after Belgium's independence from 1830 fared differently in each successor state. While in Belgium the patent system became widely used and increasingly codified, culminating in an 1850s reform, in the Netherlands the neglect of the patent system led in 1869 to its abolition.
Keywords: K22; L43; N43; O31; O34; 330; institutions; patents; economic history; nineteenth century; industrial revolution; the Netherlands; Belgium